Does a Dedicated Orthopaedic Day Surgery List Improve Delivery of Trauma Services?. Issue 11 (November 2017) - Bhamra, JS; Dhinsa, BS; Patel, S; Davies, C; Oliver, M
Our aim was to implement a 23-hour pathway for uncomplicated trauma to overcome delays and improve efficiency. A retrospective review of a single surgeon series of 105 consecutive patients operated on between July 2010 and July 2011 was performed. With recently revised trauma tariffs, we believe an efficient day surgery trauma list improves theatre utilisation, reduces inpatient bed demands, prioritises major and sub-specialist trauma and delivers patient satisfaction.